Selective Homogeneous Liquid-Liquid Extraction and Preconcentration of Thallium Using a New Calix[4]pyrrole - Reza Ghiasvand, Ali; Moradi, Farzaneh; Shadabi, Shahriar; Sharghi, Hashem; Reza Hasaninejad, Ali (Asian Journal of Chemistry, 2010)
Meso-tetraspirocyclohexylcalix[4]pyrrole (TSCC4P) was synthesized and investigated as a suitable selective complexing ligand for homogeneous liquid-liquid extraction and preconcentration of Tl+ ions. Zonyl FSA (FSA) was used as a phase separator agent under slightly acidic pH conditions. Under the optimal experimental conditions ([FSA] = 2.5% v/v, [THF] = 20.6% v/v, [TSCC4P] = 3.4 x 10-4 M and pH = 5.3), 5 I1g of Tl+ in 7 mL aqueous phase could be extracted quantitatively into 30 μL of the sedimented phase. The influence of different experimental parameters on the extraction and determination of Tl+ were investigated. The maximum concentration factor was 233-fold. The limit of detection of the proposed method was 0.004 ng/mL. The reproducibility of the proposed method was at most 3.4%. The proposed method was applied to the extraction and determination of Tl+ in different synthetic and human hair samples.